Membrane-free desalination using ionic hydrogels - Xiong, Wei. (2013)
This report exhibits our attempt to discover a membrane-free desalination approach using ionic hydrogels. Ionic hydrogels (cross-linked polyelectrolyte network) will swell in contact with water or brackish water, and an uneven distribution of salt ions within and out of the gels will be resulted in, i.e. the mobile ion concentration of the inner solution will be lower than that of the external solution. Therefore, desalination was achieved by the incorporation of salt depleted water into ionic hydrogels and the subsequent dewatering. The influence of different types of monomers, initial monomer concentration, degree of cross-linking, gel particle size and concentration of salt solution on the desalination process were studied. Possible optimum conditions for the desalination by using polyelectrolyte hydrogels are discussed. The attempt to incorporate thermally responsive properties for dewatering with low energy consumption and high water recovery compared with mechanical dewatering method is described in the report as well.